Sands of Sahara after LASIK in Avellino Corneal Dystrophy. (2nd February 2012) - Mantelli, Flavio; Lambiase, Alessandro; Di Zazzo, Antonio; Bonini, Stefano
Abstract : We report the case of a patient diagnosed with Avellino corneal dystrophy (ACD) who developed diffuse interstitial keratitis following excimer laser insitu keratomileusis (LASIK). ACD is an autosomal dominant corneal dystrophy characterized by multiple asymmetric stromal opacities that impair vision. Accepted treatments for this condition include corneal transplantation and phototherapeutic keratectomy (PTK). Our patient underwent LASIK at another institution to correct myopia. LASIK and photorefractive keratectomy (PRK) are usually contraindicated in ACD for the high risk of disease recurrence and postoperative complications. The patient came to our attention lamenting blurry vision, decreased visual acuity, and photophobia. Ophthalmologic examination revealed bilateral interstitial keratitis, also known as "sands of Sahara", a seldom-seen complication of LASIK characterized by fine and diffuse granular infiltrates at the surgical flap interface.The risk of developing interstitial keratitis, as in the case presented here, represents another valid reason for avoiding LASIK in patients with ACD.